Analysing investment and disinvestment decisions under uncertainty, firm heterogeneity and tradable output permits - Jan-Henning Feil; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2016)
This paper develops an agent-based real options model, which is capable of analyzing the investment and disinvestment decisions of heterogeneous competing firms under consideration of tradable output permits. A permit market is integrated into the model in which the firms can trade permits with each other according to their investment or disinvestment behavior for production capacity. The empirical application of the model to the EU dairy sector shows that (changes in) tradable output permit systems can have considerable effects on investments and disinvestments, in particular in markets with a high degree of firm heterogeneity. Amongst others, they can ceteris paribus increase both the willingness to invest and to disinvest especially of the less efficient firms in a market. The results shed new lights on the ongoing public debate about the potential effects of tradable output permit systems on structural change in a sector.
Keywords: 330; investment and disinvestment; real options; firm heterogeneity; tradable output permits